MODÉL PANGAJARAN WORD SQUARE PIKEUN NGARONJATKEUN KAMAMPUHNULIS AKSARA SUNDA : Studi Kuasi Eksperimen ka Siswa Kelas X-A SMA Negeri 1 Nanggung Kabupaten Bogor Taun Ajaran 2014/2015 - Rizky, Malia Julianty (2015)
This research aims to measure student learning outcomes and learning model application. The model used in this research is word square model to Sundanese script writing learning. The method use in this research is quasi-experimental method. The data source in this research is the result of Sundanese script writing in X-A class, 1 Senior High School of Nanggung, Bogor District in 2014/2015 education period, with 14 male students and 16 female students. The technique used is test technique, and the instrument used is written test sheet. The research result show that the mean of writing Sundanese scores of X-A class, 1 Senior High School of Nanggung, Bogor District before using word square learning model had not reached the Minimum Completeness Standard (63,24), while the mean of writing Sundanese scores after using word square learning model has been reached Minimum Completeness Standard (82,52). Based on the hypothesis test obtains tcount (10,14) > ttable (2,46), it shows that word square learning model might increase (19,82%) the score of X-A class, 1 Senior High School of Nanggung, Bogor District in 2014/2015 education period on the topic of writing Sundanese script. Keywords: word square learning model, writing Sundanese script Penelitian ini bertujuan untuk mengukur peningkatan hasil belajar siswa dan penggunaan model pembelajaran. Model yang digunakan dalam penelitian adalah model pembelajaran word square pada pembelajaran menulis aksara Sunda. Metode yang digunakan dalam penelitian ini adalah metode kuasi eksperimen. Sumber data dalam penelitian ini adalah hasil nilai menulis aksara Sunda siswa kelas X-A SMA Negeri 1 Nanggung Kabupaten Bogor taun ajaran 2014/2015, dengan jumlah 14 orang siswa laki-laki dan 16 orang siswa perempuan. Tekhnik yang digunakan adalah tekhnik tes, dengan instrumen lembar soal tes tulis. Berdasarkan hasil penelitian diketahui rata-rata hasil nilai menulis aksara Sunda siswa kelas X-A SMA Negeri 1 Nanggung Kabupaten Bogor taun ajaran 2014/2015 sebelum menggunakan model pembelajaran word square yaitu belum mampuh (63,24) mencapai KKM , sedangkan rata-rata hasil nilai menulis aksara Sunda setelah menggunakan model pembelajaran word square yaitu sudah mampuh (82,52) mecapai KKM. Dari hasil uji hipotesis diperoleh thitung (10,14) > ttabel (2,46), hal ini menunjukkan bahwa model pembelajaran word square dapat meningkatkan (19,28%) hasil nilai siswa kelas X-A SMA Negeri 1 Nanggung Kabupaten Bogor taun ajaran 2014/2015 pada pembelajaran menulis aksara Sunda. Kata Kunci: model pembelajaran word square, menulis aksara Sunda